Reduction According to Sibawayh - Al Suleiman, Hind Abdel Aziz (Arts for Linguistic & Literary Studies, 2024)
This study explores the concept of 'reduction' as described by Sibawayh and its interrelation with deletion, implicitness, and substitution. It investigates how reduction is influenced by the speaker's emotional state and its impact on the listener. Employing a descriptive and analytical methodology, the research delves into Sibawayh's usage of reduction in specific linguistic contexts where verbs are implied or substituted, shedding light on how it conveys verb meanings and reflects the speaker's intentions. The findings reveal that the presence of verbal substitutes in reduced constructions signifies recurring linguistic patterns that convey verb meanings and structural relationships. Furthermore, the study illustrates that reduction, implicitness, and deletion often converge in not mentioning or showing, with deletion encompassing a broader scope, applicable both in compositional and non-compositional contexts. Implicitness, on the other hand, primarily operates within compositional structures, whereas reduction representing a distinctive form of implicitness contingent upon the implicitness of the verb or its surrogate. It underscores reduction as a cognitive process influenced by the speaker's emotional state, emphasizing linguistic efficiency and semantic clarity.